Prevalence of Anti-Toxoplasma gondii and Anti-Brucella Spp. Antibodies in Pregnant Women From Mogadishu, Somalia - Yusuf, Abdulkarim A.; Hassan-Kadle, Ahmed A.; Ibrahim, Abdalla M.; Hassan-Kadle, Mohamed A.; Yasin, Abdullahi M.; Khojaly, Maha; Garcia, João L.; Vieira, Rafael F. C. (Frontiers in Reproductive Health, 2021)
Toxoplasmosis and brucellosis are zoonotic diseases of worldwide distribution. They both cause abortion and infertility in human and animals. Limited data are available about these pathogens in Somali people and their animals. Hence, this study has evaluated the prevalence of anti-Toxoplasma gondii and anti-Brucella spp. antibodies in pregnant women in Mogadishu, Somalia. Serum samples from 307 pregnant women from Mogadishu, Somalia were tested for anti-T. gondii antibodies by Latex Agglutination Test (LAT) and anti-Brucella spp. antibodies by Rose Bengal Plate Test (RBPT) and a commercial competitive-ELISA (cELISA). A total of 119/307 (38.76%) pregnant women had a prior history of abortion. A total of 159/307 (51.79%; 95% CI: 46.2–57.35%) pregnant women were seroreactive for T. gondii by LAT at different stages of pregnancy. For Brucella spp., when RBPT and cELISA were combined four/307 (1.30%; 95% CI: 0.36 – 3.30%) pregnant women were seroreactive to anti-Brucella spp. antibodies, being 2/307 (0.65%; 95% CI: 0.18 – 2.34%) by RBPT and 3/307 (0.98%; 95% CI: 0.33 – 2.83%) by cELISA. Two women were seroreactive for both agents. A high seropositivity to T. gondii and low seropositivity to Brucella spp. have been found in pregnant women from Mogadishu, Somalia. Considering the high number of abortions in the country associated to the fact that awareness on other zoonotic abortifacient pathogens in Somalis is very low, further studies should be conducted to evaluate the potential causes of abortions.